“I wanna be like you”: testing the link between social affiliation and overimitation in infancy - Dragon, Marilyne; Poulin-Dubois, Diane (Frontiers in Developmental Psychology, 2025)
IntroductionOne way children learn is through imitation, an important ability to gain new skills and to share cultural knowledge. Overimitation, or the tendency to copy irrelevant actions to achieve a goal, is one specific type of imitation which may be particularly related to social motivations. Various theoretical accounts have been developed to explain this construct, including that one overimitates to affiliate with the demonstrator. However, it is still unclear what mechanisms underlie overimitation and how early it develops. The goal of the current experiment was to examine the emergence of overimitation in infancy and its link with social affiliation and other forms of imitation.MethodsWe administered to 16- to 21-month-olds an overimitation task adapted for infants, an elicited imitation task, an unfulfilled intentions imitation task, and an in-group preference task, used as a measure of social affiliation. We expected an association between the performance on the different imitation tasks, but a weaker link with overimitation. It was also predicted that performance on the in-group preference task would be more strongly related to the overimitation task than to the other imitation tasks.Results and discussionResults showed a significant association between the elicited and unfulfilled intentions imitation tasks, but no link between overimitation and in-group preference. To our knowledge, this is one of the first experiments to study overimitation in infancy and to attempt to find an association with other forms of imitation and with a separate and direct measure of in-group preference as a proxy for social affiliation.